Formation of cavities in the ionospheric plasma due to localized electrostatic turbulence - Chibisov, D.V. (Вопросы атомной науки и техники, 2018)
The possibility of formation of lower hybrid cavities in plasma of the terrestrial ionosphere and magnetosphere due to the interaction of plasma with inhomogeneous axially symmetric electrostatic turbulence is investigated. Heating, turbulent diffusion, as well as the drift of ions due to the radial inhomogeneity of electrostatic turbulence is considered. The equation determining the evolution of the plasma distribution function as a result of these effects is obtained. Stationary solution of this equation is found.